Katagon at Two Timings Compared to Standards in Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this trial was to compare Katagon (tolpyralate/nicosulfuron) to standard treatments for weed control in corn. Katagon plus atrazine applied early postemergence was as effective as any herbicide tested on the weeds present. When application timing was delayed to late postemergence, most herbicides were less effective. Early season corn injury was minor and did not persist. Although most herbicide treatments increased yields relative to the non-treated control, yields were generally best when any treatment was applied early postemergence.
Keywords: Residual control; corn; herbicide timing; mode of action